2002
DOI: 10.1046/j.1532-5415.2002.50458.x
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infection: Differences Between Young‐Old, Old, and Old‐Old Patients

Abstract: The differences in NBSI are important in serious infectious diseases and often require empirical antibiotic therapy. Age is also a risk factor but only for CABSI and suggests that the old-old patients represent a frail population in the community. Further prospective studies are needed to confirm these findings and analyze predisposing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 33 publications
6
49
1
Order By: Relevance
“…37 Even in the absence of an indwelling urinary catheter, higher rates of UTI in older patients may be secondary to incontinence or neurological disorders and to a higher rate of bacteremia associated with pyelonephritis in older people. 30,35,38 As presented in Table 3, most studies reported respiratory tract as the source in 9-28% of patients. An abdominal source was reported in 1-20%, depending whether a biliary source was included in the definition or not.…”
Section: Source Of Bsismentioning
confidence: 99%
See 2 more Smart Citations
“…37 Even in the absence of an indwelling urinary catheter, higher rates of UTI in older patients may be secondary to incontinence or neurological disorders and to a higher rate of bacteremia associated with pyelonephritis in older people. 30,35,38 As presented in Table 3, most studies reported respiratory tract as the source in 9-28% of patients. An abdominal source was reported in 1-20%, depending whether a biliary source was included in the definition or not.…”
Section: Source Of Bsismentioning
confidence: 99%
“…In studies including only community acquired infections, Gram negative bacteria represent up to 70% of BSIs, 20 in contrast to studies including only nosocomial BSI, in which Gram negative bacteria constitute 40-50% 3,13 but are still more common than Gram positive organisms. 41 Gram positive organisms usually represent between 30-45% of BSIs in elderly, 20,28,35 although some studies reported 55-60%. 29,40 In these studies, however, rates of methicillin resistance Staph aureus (MRSA) infection were higher compared to other studies in mixed population of community acquired and nosocomial BSIs.…”
Section: Microbiology Of Bsismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, dementia, instability of gait, falls, and swallowing disorders also increase with age. These conditions add to morbidity and higher mortality from infectious diseases [5,[26][27][28][29]. Lastly, there are specific communal challenges that occur in infections in the elderly.…”
Section: An Overview Of Infections In the Elderly And Ltcfsmentioning
confidence: 99%
“…[1][2][3][4] Staphylococcus aureus bloodstream infection (SAB) represents a significant burden in terms of morbidity and mortality for older adults. Major risk factors associated with the development of SAB includes the presence of comorbid illnesses, such as congestive heart failure, chronic kidney disease, and diabetes mellitus, and the use of medical devices.…”
mentioning
confidence: 99%